The relationship between multimorbidity and cognitive function in older Chinese adults: based on propensity score matching - Zhang, Yumeng; Yuan, Xiaoli; Jiang, Zhixia; Hu, Rujun; Liang, Heting; Mao, Qingyun; Xiong, Yan; Zhang, Jiabi; Liu, Mi (Frontiers in Public Health, 2024)
Objective: The goal of this study was to further validate the effect of multimorbidity on cognitive performance in older adults after controlling for confounders using propensity score matching (PSM). Methods: A cross-sectional survey of elderly people aged 60 years or older selected by convenience sampling was conducted in seven medical institutions, three communities, and five nursing homes in Zunyi City, Guizhou Province. The data collected included general information, health-related information, and Mini-Mental State Examination (MMSE) scores. Variables were controlled for confounders by PSM to analyze differences in cognitive ability between multimorbidity and nonmultimorbidity older adults. Logistic regression and multivariate-adjusted restricted cubic spline (RCS) curves for matched samples were used to assess the relationship between multimorbidity and cognitive decline. Results: A total of 14175 respondents were enrolled, and the mean age of the participants included in this study was 71.26±7.1 years, including 7170 (50. 58%) of the participants were males, 7005 (49.42%) were females, and 5482 participants (38.67%) were screened for cognitive decline. After PSM, logistic regression analysis revealed that multimorbidity was a risk factor for cognitive decline (OR=1.392, 95% CI=1.271-1.525, P<0.001). The RCS show that the risk of cognitive decline is always greater in older adults with multimorbidity than in older adults without multimorbidity at the same age. Age, sex, marital status, educational level, monthly income, drinking status, participation in social activities, and exercise were influential factors for cognitive decline in older adults (P<0.05). The incidence of cognitive decline in older adults with multimorbidity was also greater than that in older adults with one chronic disease (P<0.001). Conclusion: The risk of cognitive decline in older adults with multimorbidity is greater than that in older adults without multimorbidity; therefore, the government should strengthen the prevention and treatment of multimorbidity in older adults to further protect their cognitive abilities.